1996
DOI: 10.1007/bf01369789
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MHS-5 in detecting seminal fluid in vaginal swabs

Abstract: Vaginal swabs taken in 211 cases of alleged sexual assault were examined for seminal vesicle-specific antigen (SVSA) using an MHS-5-ELISA (SEMA kit). The results were compared with those obtained by sperm detection by means of light microscopy and the acid phosphatase reaction (ACP), using Phosphatesmo-KM papers. Especially in fresher samples (duration of storage between 10 days and 2 1/2 months), a high degree of correlation was observed between the results of light microscopic and MHS-5 methods. Several case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
14
1
1
Order By: Relevance
“…The MHS-5 antibody, which recognizes a specific Sg I epitope, is available commercially as an immunoassay kit for the detection of semen in forensic specimens. Its value rests principally on its high specificity for semen, its stability and its presence in semen from normal and vasectomized men [38,89,90]. In addition, the same antibody has also been used as a specific and reliable tool for the diagnostic of agenesis of the seminal vesicles and vas deferens [91], due to its specific reactivity with secretions of the seminal vesicles.…”
Section: Applications and Benefits Derived From Sg Imentioning
confidence: 99%
“…The MHS-5 antibody, which recognizes a specific Sg I epitope, is available commercially as an immunoassay kit for the detection of semen in forensic specimens. Its value rests principally on its high specificity for semen, its stability and its presence in semen from normal and vasectomized men [38,89,90]. In addition, the same antibody has also been used as a specific and reliable tool for the diagnostic of agenesis of the seminal vesicles and vas deferens [91], due to its specific reactivity with secretions of the seminal vesicles.…”
Section: Applications and Benefits Derived From Sg Imentioning
confidence: 99%
“…There is another fragment of Sg, the antigen recognized by the monoclonal mouse anti‐human sperm antibody 5 (MHS‐5). This antibody was originally raised against whole spermatozoa but was found to recognize a sperm‐coating antigen originating from the seminal vesicles (Herr et al, 1986; McGee and Herr, 1987, 1988) and was used for MHS‐5‐enzyme‐linked immunosorbent assay (ELISA) to detect human semen in forensic samples (Herr and Woodward, 1987; Keil et al, 1996). However, no study has reported on the quantification of Sg in seminal plasma with the MHS‐5‐ELISA system.…”
mentioning
confidence: 99%
“…From these studies, a number of different factors have been shown to affect time range estimates of detection (6). However, it is generally agreed that spermatozoa will, on average, persist longer than other seminal fluid markers (6,18,31,34,35). The detection of seminal fluid markers such as PSA and SVSA at high concentrations is generally considered indicative of the presence of semen in the absence of spermatozoa (11)(12)(13)(14)31).…”
Section: Discussionmentioning
confidence: 99%
“…The development of monoclonal antibody-based systems with predefined specificity to definite antigens has greatly advanced our ability to preferentially discriminate between specific markers of interest (36) and, thus, to attribute source to unknown biological stains in forensic casework (7,11,13,15,16,18,19,21,25,26,31,37). Several fluorescent dyes, each with their own ideal performance parameters, have been introduced for use in immunofluorescence (38).…”
mentioning
confidence: 99%